Evolving trends in psychiatric emergency services in Southern China: a seven-year retrospective analysis - Cuiling Zhang; Suiyun Weng; Xiaoyu Zhang; Songkang Liu; Min Yu; Miaoling Jiang (International Journal of Emergency Medicine)
Abstract Background The Affiliated Brain Hospital, Guangzhou Medical University is an important provider of psychiatric emergency services (PES) in southern China. Revealing the evolution trend of the psychiatric emergency services of this hospital can help decision-makers formulate relevant policies. However, at present, there is a lack of large-scale, long-term retrospective studies. Methods A retrospective analysis was conducted on patient records from the psychiatric emergency room (PER) of the Affiliated Brain Hospital, Guangzhou Medical University. Data included demographic and clinical variables were aggregated annually and described using percentages from 2018 to 2024. Chi-square and Fisher’s exact test were used to confirm significance of the trends. Results More voluntary health-seeking behaviors, broader medical insurance coverage, more cautious use of restraint measures, and more precise diagnoses were observed from 2018 to 2024. Besides, there were an increasing number of younger, highly educated, unmarried, and unemployed visitors. We also found that the gender gap is widening and medical resources are increasingly strained. There are differences between judicial and medical personnel in making compulsory decisions. During Covid-19, the demographic and clinical variables show significant changes. Conclusions PES in southern China have developed to a certain extent, but they are also confronted with obstacles at the same time. These trends underscore the need for enhanced referral systems, expanded community-based psychiatric care, ethical guidelines for managing coercive measures and strengthening the response strategies for public event crises.